Management of Recurrent Osteoid Osteoma: Case Report - Trupthi Das; M.C. Uthappa; Ravikanth Devathu (Journal of Clinical Interventional Radiology ISVIR)
Osteoid osteoma is a benign bone tumor accounting for 10% of all benign bone tumors and 2 to 3% of all primary bone tumors. Pain is the predominant presenting symptom demanding medical attention. Radiofrequency ablation has become the standard line of treatment due to its high clinical success rate. Although it is highly effective, the recurrence rate is estimated to be in the range of 7 to 16.3%, with younger individuals having higher recurrence rates. We report a unique case of recurrent osteoid osteoma with a metachronous lesion in a female child for which radiofrequency ablation of both the lesions was performed, which proved to be effective.